Gender and the European union - Kantola, Johanna 1977- (The European Union series., 2010)
"This broad ranging new text provides a systematic assessment of the emergence of gender as a significant issue on the EU agenda and of the EU's impact on gender inequality, both in terms of specifically gender-related policies and the gender dimensions of other policies"--Provided by publisher.